2020
DOI: 10.1091/mbc.e19-09-0520
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput gene screen reveals modulators of nuclear shape

Abstract: Using a high-throughput RNAi screen of epigenetic regulators combined with an automated elliptical Fourier analysis, we identify genes required for the maintenance of nuclear shape in breast epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 60 publications
5
31
0
Order By: Relevance
“…Our data show that HP1α is one of the likely many possible chromatin crosslinking elements in the genome. There is a growing list of chromatin proteins and nuclear components contributing to maintenance of nuclear morphology, some of which have been identified by a genetic screen for effects on nuclear morphology ( Tamashunas et al, 2020 ) and a variety of other experiments (reviewed in Stephens et al, 2019a ). Other chromatin crosslinkers to be investigated include chromatin looping proteins and other components implicated by various experiments, such as cohesin, CTCF, mediator, and possibly RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that HP1α is one of the likely many possible chromatin crosslinking elements in the genome. There is a growing list of chromatin proteins and nuclear components contributing to maintenance of nuclear morphology, some of which have been identified by a genetic screen for effects on nuclear morphology ( Tamashunas et al, 2020 ) and a variety of other experiments (reviewed in Stephens et al, 2019a ). Other chromatin crosslinkers to be investigated include chromatin looping proteins and other components implicated by various experiments, such as cohesin, CTCF, mediator, and possibly RNA.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in chromatin-based nuclear mechanics can, independently of lamins, cause abnormal nuclear morphology, which is a hallmark of human disease (Stephens et al, 2019a). A recent high-throughput screen revealed that many key chromatin proteins also contribute to nuclear shape (Tamashunas et al, 2020), raising the question of the relative roles of histone modifications versus chromatin proteins such as HP1α. Recent experimental and modeling studies suggest chromatin proteins, like HP1α, may contribute to mechanics by acting as physical linkers.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, deviations from control values in nuclear geometrical descriptors, i.e ., major and minor axes (Fig. 4D), might indicate deformations and irregularities due to altered cytoskeleton or chromatin regulation [52]. LiveCellMiner automatically detects interphase to prophase and metaphase to anaphase transitions as well as the degree of rotation of the chromatin mass (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the depletion of certain cytoskeletal-associated proteins [80, [114][115][116][117][118], the transcription factor GATA6 [119], the ER-localized LEM protein, ANKLE2 [63], and the SPANX cancer/testis antigen [122] each led to altered nuclear appearance. This list is not meant to be all-inclusive and other publications have identified additional proteins that regulate nuclear morphology [109,213,214]. While many proteins in Table 1 directly impact the structure of the nuclear envelope or lamina (e.g., lamins, LEM proteins), several of the listed proteins affect nuclear morphology indirectly.…”
Section: Mechanisms Of Alterations In Nuclear Morphologymentioning
confidence: 99%